RANCANG BANGUN ALAT PENDETEKSI GOLONGAN DARAH DAN SATURASI OKSIGEN BERBASIS ARDUINO UNO - Ahmad Halim; Ganis Sanhaji; Yudha Aria Praja (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
In this study a device was designed to detect human blood group using the ABO method which is integrated with a blood oxygen saturation meter. This tool can detect agglutination or non-agglutination reactions in blood samples that have been treated with antisera and will then be read by three TCRT5000 sensors which are reflective sensors used as detectors of A, B and Rhesus antigens when agglutination and non-agglutination reactions occur on paper. blood sample test. In addition, the MAX30100 sensor is also used to measure blood oxygen saturation in the human body. Data that has been read by the sensor will be directly processed by Arduino Uno and the results from reading by the sensor will be displayed on the 16x2 LCD. In testing the human blood group detector designed where the results of all tests on the respondent's blood samples totaling 8 blood samples obtained a success value of 100%. In addition, the results of testing the Oxygen Saturation Measuring Instrument using the MAX30100 sensor obtained an accuracy value of 99.53%.